[tex]3/ 5x^6*y^6[/tex] is the solution f the expression [tex](-9x^-1*y^-9) / (-15x^5*y^-3)[/tex]
Given expression:
(-9x^-1*y^-9) / (-15x^5*y^-3)
As we know, any number with negative power can be written in inverse form with positive power.
[tex]x^-a = 1/x^a[/tex]
Two number having same base their powers are added:
[tex]x^a + x^b = x^a+b[/tex]
[tex]= > (-9x^-1*y^-9) / (-15x^5*y^-3)= (-3x^-1*y^-9) / (-5x^5*y^-3)\\=3/(5x^6 y^6)[/tex]
Hence the solution would be [tex]3 (5x^6 y^6)[/tex].
Learn more about Expression on:
https://brainly.com/question/1280754
#SPJ4